Influences on foreign equity ownership level in joint ventures in Vietnam. - Ng, Pei San. (2008)
This study examines the factors that determine the level of foreign equity ownership in joint ventures in Vietnam. Drawing upon Dunning's ownership, locational and internalization paradigm and the literature on bargaining power, ten variables that may have impacts on foreign ownership preferences and concessions are examined.